2020
DOI: 10.3389/fmicb.2020.00214
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of the Zika Virus Crossing the Placental Barrier and the Blood-Brain Barrier

Abstract: Zika virus (ZIKV) infection causes severe neurological symptoms in adults and fetal microcephaly and the virus is detected in the brain of microcephaly and meningoencephalitis patient. However, the mechanism of ZIKV crossing the physiological barrier to the central nervous systems (CNS) remains elusive. The placental barrier and the blood brain barrier (BBB) protect the fetus from pathogens and ensure healthy brain development during pregnancy. In this study, we used human placenta trophoblasts cells (JEG-3) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 46 publications
(55 reference statements)
2
82
2
Order By: Relevance
“…Many authors have reported on the capacity of ZIKV to infect neurons and other neuronal cells that most likely detrimentally affect their function and contribute to congenital Zika syndrome (CZS), which has as its main characteristics microcephaly and ventriculomegaly ( 1 , 3 5 , 7 , 8 ). In this scenario, studies aiming to understand the mother-fetus interface of ZIKV vertical transmission have been strongly recommended ( 9 ). In the vertical transmission, one major barrier is the placenta, a highly specialized organ that ensures the fetus’ development, by allowing the exchange of nutrients, solutes and acting as physiological barrier against toxic molecules and pathogens, such as viruses ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have reported on the capacity of ZIKV to infect neurons and other neuronal cells that most likely detrimentally affect their function and contribute to congenital Zika syndrome (CZS), which has as its main characteristics microcephaly and ventriculomegaly ( 1 , 3 5 , 7 , 8 ). In this scenario, studies aiming to understand the mother-fetus interface of ZIKV vertical transmission have been strongly recommended ( 9 ). In the vertical transmission, one major barrier is the placenta, a highly specialized organ that ensures the fetus’ development, by allowing the exchange of nutrients, solutes and acting as physiological barrier against toxic molecules and pathogens, such as viruses ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, studies aiming to understand the mother-fetus interface of ZIKV vertical transmission have been strongly recommended ( 9 ). In the vertical transmission, one major barrier is the placenta, a highly specialized organ that ensures the fetus’ development, by allowing the exchange of nutrients, solutes and acting as physiological barrier against toxic molecules and pathogens, such as viruses ( 9 , 10 ). Estimates are that the viral genome can be detected in the placenta of 20–50% of pregnant women exposed to ZIKV ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo ( 3 8 ) and in vitro ( 9 11 ) studies have demonstrated that ZIKV replicates in the placenta, in the brain tissues of fetuses with microcephaly, or in placenta-derived primary cells. However, knowledge of the mechanism through which ZIKV infects and replicates in the placenta remains elusive ( 12 , 13 ). ZIKV, similarly to other flaviviruses, has a single-stranded positive-sense RNA genome of approximately 11 kb that is translated into a single large polyprotein, and this polyprotein is cleaved into individual proteins at the rough endoplasmic reticulum (ER) ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, peripheral blood mononuclear cells were identified as important cellular targets of American ZIKV strain infection, and for promoting ZIKV spread 39 . It is important to note that astrocytes are functional elements in the BBB, thus these cells can contribute to propagation and progress of ZIKV infection, causing injury of neural cells through direct infection-induced and/or indirect immune-mediated mechanisms 40 42 .…”
Section: Discussionmentioning
confidence: 99%